The glycoside hydrolase gene family profile and microbial function of Debaryomyces hansenii Y4 during South-road dark tea fermentation - Zou, Yao; Liu, Minqiang; Lai, Yuqing; Liu, Xuyi; Li, Xian; Li, Yimiao; Tang, Qian; Xu, Wei (Frontiers in Microbiology, 2023)
Microbes are crucial to the quality formation of Sichuan South-road Dark Tea (SSDT) during pile-fermentation, but their mechanism of action has not yet been elucidated. Here, the glycoside hydrolase (GH) gene family and microbial function of Debaryomyces hansenii Y4 during solid-state fermentation were analyzed, and the results showed that many GH genes being distributed in comparatively abundant GH17, GH18, GH76, GH31, GH47 and GH2 were discovered in D. hansenii. They encoded beta-galactosidase, alpha-D-galactoside galactohydrolase, alpha-xylosidase, mannosidase, etc., and most of the GHs were located in the exocellular space and participated in the degradation of polysaccharides and oligosaccharides. D. hansenii Y4 could develop the mellow mouthfeel and “reddish brown” factors of SSDT via increasing the levels of water extracts, soluble sugars and amino acids but decreasing the tea polyphenols and caffeine levels, combined with altering the levels of thearubiins and brown index. It may facilitate the isomerization between epicatechin gallate and catechin gallate. Moreover, the expression levels of DEHA2G24860g (Beta-galactosidase gene) and DEHA2G08602g (Mannan endo-1,6-alpha-mannosidase DFG5 gene) were sharply up-regulated in fermentative anaphase, and they were significantly and negatively correlated with epicatechin content, especially, the expression of DEHA2G08602g was significantly and negatively correlated with catechin gallate level. It was hypothesized that D. hansenii Y4 is likely to be an important functional microbe targeting carbohydrate destruction and catechin transformation during SSDT pile-fermentation, with DEHA2G08602g as a key thermotolerant functional gene.